Investigation on transvorial transmission of chikungunya and dengue viruses in the wild population of Aedes mosquitoes at selected rural localities in Kuching Sarawak, Malaysia - Nor Aliza Abdul Rahim,; Tan, Cindy Siew Ching; Anna Andrew, (Pusat Sistematik Serangga, Universiti Kebangsaan Malaysia, 2022)
Chikungunya virus (CHIKV) and dengue virus (DENV) are mosquito-borne viruses transmitted by Aedes aegypti and Aedes albopictus. CHIKV has become endemic in Malaysia since its reemergence in 2006, whereas DENV was first reported in Malaysia in 1902. In 2009, Kampung Pulau Salak in Kuching, Sarawak, Malaysia was one of the areas affected by chikungunya outbreak. Hence, this study was conducted to investigate the potential vector and determine the presence of CHIKV and DENV transovarial transmission among the mosquito population in Kampung Pulau Salak and Kampung Tanjong Bako, Kuching, Sarawak. Mosquito larvae were collected from ovitraps and discarded receptacles found in both villages. The emerged Aedes mosquitoes were pooled (223 pools) according to sex, species, and study site before being subjected to RNA extraction and two-step reverse-transcription polymerase chain reaction (RT-PCR). The species of Aedes mosquito caught in both villages were Ae. albopictus and Ae. aegypti which comprises 95.8% and 4.2% of the total number of Aedes mosquito collected respectively. CHIKV was detected in one male and one female pool of the emerged adults of Ae. albopictus collected from Kampung Pulau Salak, which belongs to the East/Central/South/African (ECSA) genotype, whereas DENV serotype 2 (DENV-2) was detected in one pool of male and two pools of female of emerged Ae. albopictus collected from the same village. CHIKV and DENV were not detected in the emerged Aedes mosquitoes collected from Kampung Tanjong Bako. The presence of CHIKV and DENV in the emerged adults of mosquitoes revealed evidence of transovarial transmission among the population of Ae. albopictus in Kampung Pulau Salak, and because Ae. albopictus is the major species collected from the site, this study indicates that the species may be the primary vector of the viruses in the village.